Entrepreneuship Profile Evaluation using the Meaning of Psycological Types - Licht, René Henrique Götz; Oliveira, Paulo Sérgio Gonçalves de; Ventura, Vera Lúcia da Silva (Review of Business Management, 2007)
This paper presents a study about the psychological types of entrepreneurs employing the psychological type theory developed by Carl Gustav Jung. The psychological types of the entrepreneurs were obtained by means of the Kersey & Bates inventory of personality. The results of the type distribution show that entrepreneurs prefer the Extravert (E) attitude, prefer to gather information by means of the Sensation (S) function, make decisions by means of the Feeling (F) function and prefer to interact with others by means of the Judgment (J) process. Key-words: Entrepreurship. Psychological Types. Entrepreneur.